2013
DOI: 10.1136/bcr-2013-009311
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome with documented hyponatraemia

Abstract: We present a case of a 78-year-old African-American man with a history of hypertension, and with no prior history of seizure. The patient presented with hypertensive urgency as well as stroke such as symptoms of confusion, seizure, postictal confusion, left hemianopsia and hyponatraemia. MRI findings were suggestive of posterior reversible encephalopathy syndrome (PRES). The patient was treated with appropriate medications with the resolution of his stroke-like symptoms. This case report discusses a patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Several other chemotherapeutic agents used in the treatment of ALL have also been associated with PRES, most likely through cytotoxic mechanisms . Increasing data indicate that hyponatremia might contribute to the pathogenesis of PRES . The underlying mechanism could be disturbance in the regulation of osmolality in the brain and altered water circulation via the water‐channel protein aquaporin‐4, even in a mildly hyponatremic environment…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other chemotherapeutic agents used in the treatment of ALL have also been associated with PRES, most likely through cytotoxic mechanisms . Increasing data indicate that hyponatremia might contribute to the pathogenesis of PRES . The underlying mechanism could be disturbance in the regulation of osmolality in the brain and altered water circulation via the water‐channel protein aquaporin‐4, even in a mildly hyponatremic environment…”
Section: Discussionmentioning
confidence: 99%
“…9,25,30,31,[34][35][36][37][38][39][40][41][42][43] Increasing data indicate that hyponatremia might contribute to the pathogenesis of PRES. 4,44,45 The underlying mechanism could be disturbance in the regulation of osmolality in the brain 46 and altered water circulation via the water-channel protein aquaporin-4, 4,47 even in a mildly hyponatremic environment. 46 Seizures are the most frequent symptom at PRES presentation, often with distinct EEG findings.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of blood vessels function for the homeostasis of the brain, little is known about the influence of hyponatremia on cerebrovascular regulation 7. One previous study demonstrated that the dilatation of the cerebral vessel in response to acetylcholine, which is endothelium and nitric oxide dependent, was severely impaired in hyponatremia 8.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior reversible encephalopathy syndrome (PRES) first described by Hinchey J et al in 1996 is a reversible neurological condition characterized by seizures, impaired consciousness and visual defecit with a typical radiologic findings on computed tomographic (CT) and magnetic resonance imaging (MRI) of brain. [1][2][3][4][5][6] There are described risk factors associated with developing this clinical syndrome, typically occurring mostly in females across all ages, ranging from 4-90years of age, 3 with renal disease, hypertension in pregnancy and as seen in patients on immune suppresive therapies. 6 It is also thought to follow a hypovolaemic episode in infection, sepsis, autoimmune disease and electrolyte abnormalities in septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of the neurological symptoms in this patient, describes the natural history of PRES, which is self limiting and patient recovers without permanent neurological deficit. 5 It is important to exclude organic causes of neurological signs in surgical patients as we did with radiologic imaging.…”
Section: Discussionmentioning
confidence: 99%